أثر الانتماء الحزبي والمنتطقي في ازدياد ظاهرة الطلاق في زنجبار: دراسة مقاصدية = Party and regional affiliations in increasing the phenomenon of divorce in Zanzibar: a maqasidic study - Ramadhan, Bilal Jum'ah; Arif, Arif Ali; Ibrahim Mohamed, Hossam El Din (2018)
This study deals with the impact of party affiliation on the rise of the phenomenon of divorce in Zanzibar. It also provides a historical overview of the entry of Islam, its economy and history of political parties before and after independence of the country. Pointing to the high rate of divorce in Zanzibar, this study identifies major reasons behind it, which include affiliation to various political parties, discrimination based on the variances of islands, ignorance about religious teachings, inefficient knowledge about the purposes of familial relationships, regional chauvinism and political party racism. The statement of the problem in this research is that in contrast to rest of countries, the high rate of divorce phenomenon in Zanzibar is repercussion of the affiliation to various political parties and belonging to different islands. Likewise, this study digs out the motives of this problem which causes the disintegration of families and its solutions in light of maqāṣid al-Sharīʿah. This research contains three chapters. The first chapter analyses the history of advent of Islam and political parties to Zanzibar; second chapter deliberates on consequence of political affiliation in the rise of divorce rate in Zanzibar and third chapter discusses the role of maqāṣid al-Sharīʿah in reducing the occurrence of divorce because of party and regional affiliations.